Urinary Proteomics Identifying Novel Biomarkers for the Diagnosis of Adult-Onset Still’s Disease - Sun, Yue; Wang, Fan; Zhou, Zhuochao; Teng, Jialin; Su, Yutong; Chi, Huihui; Wang, Zhihong; Hu, Qiongyi; Jia, Jinchao; Liu, Tingting; Liu, Honglei; Cheng, Xiaobing; et al. (Frontiers in Immunology, 2020)
Adult-onset Still's disease (AOSD) is a systemic, multigenic autoinflammatory disease and the diagnosis of AOSD must rule out neoplasms, infections, and other autoimmune diseases. Development of a rapid, efficient but noninvasive diagnosis method is urgently needed for improving AOSD therapy. In this study, we first performed a urinary proteomic study using isobaric tags for relative and absolute quantification (iTRAQ) labeling combined with LC-MS/MS analysis in patients with AOSD and healthy control (HC) subjects. The urinary proteins were enriched in pathways of the innate immune system and neutrophil degranulation, and we identified that the alpha-1-acid glycoprotein 1 (LRG1), orosomucoid 1 (ORM1) and ORM2 proteins were highly expressed in patients with AOSD. The elevated urine levels of LRG1, ORM1, and ORM2 were further validated by enzyme-linked immunosorbent assay in active patients with AOSD, disease controls and HC subjects. Receiver operating characteristic (ROC) curves showed that the areas under the curve (AUCs) of LRG1, ORM1 and ORM2 were 0.700, 0.837 and 0.736, respectively (all p < 0.05). Furthermore, we found that the urine levels of LRG1, ORM1, and ORM2 were positively correlated with the systemic score and erythrocyte sedimentation rate (ESR) and that the urine levels of LRG1 were positively correlated with interleukin (IL)-1β, IL-6 and IL-18 levels, while the urine levels of ORM1 were positively correlated with the IL-1β level. Together, our study identified novel urinary markers for noninvasive and simple screening of AOSD.